Web-Based Employee Leave Information System Application Design At Pt Arai Rubber Seal Indonesia - Dirman Dirman; Reksa Anugrah; Hera Faisal Rachmat; Adiyanto Adiyanto (UJoST- Universal Journal of Science and Technology, 2022)
The presence of computers is felt to be very important in life. Computers were created none other than to help humans in terms of problem solving. Currently, many companies have used a computerized system as one of the tools used in an effort to develop and expand the company. Along with the rapid development of technology, web-based information systems are used as a means of increasing information. Utilization will facilitate a job as well as faster data processing, decisions to be taken more precisely, save time and costs. In addition, a web-based information system can also be an efficient means of promotion and a source of information that can be accessed by increasingly widespread internet users. PT Arai Rubber Seal Indonesia is a company engaged in manufacturing (rubber industry) which produces automotive components and other finished goods from synthetic rubber. Currently employs 970 employees to make products continuously in line with the increasing number of customers and orders in Indonesia and outside Indonesia, with a three shift work division system. The products produced include Oil Seal & Valve Steam Seal, O-Ring & Rubber Part as much as 500,000,000/year. The business processes used are already using IT, starting from the manufacturing process and how the divisions work. Our deep industry experience, coupled with many other important capabilities have enabled us to deliver high quality, efficient and cost effective and integrated technology solutions. The design method of the web-based employee leave information system application at PT. Arai rubber seal Indonesia used in this study is UML (Unified Modeling Language) which will be developed using the PHP programming language and MySQL database. The system development method uses the SDLC (System Development Life Cycle) waterfall model. The online leave system created can simplify the process of submitting and approving leave. With the online leave system, the process for submitting leave proposals can be done without having to meet face to face. By using the online leave system, the process of making employee leave reports becomes easier and storing employee leave history data can be printed at any time because it is already stored in the database.